Isolation of reactive Red 3BX and Yellow 4GL dye degrading bacteria from the textile sludge - Fahim, Ahmed Abdullah (BRAC University, 2016)
This thesis report is submitted in partial fulfillment of the requirement for the degree of Bachelor of Science in Biotechnology, 2015.